2019
DOI: 10.1021/acs.chemmater.9b04206
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electrochemical Mg-Ion Activity in MgCr2–xVxO4 Spinel Oxides

Abstract: Mg migration in oxide spinels is impeded by strong affinity between divalent Mg and oxygen, suggesting a necessity of exploring new chemistry of solid lattices for functional Mg-ion electrode materials. Cationic mobility with a suitable activation energy in Cr spinels is evidenced by theoretical and experimental results, while redox potentials of V are appropriate to operate with currently limited candidates of nonaqueous electrolytes. By controlling the structure, composition, and complexity, a largely solid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 43 publications
1
67
0
Order By: Relevance
“…47 This observation suggests that the V 2 O 5 -TiO 2 composite not only possessed smaller crystallite sizes than the V 2 O 5 sample, but a greater degree of crystalline disorder. 28 Electrochemical analysis of the two materials under study was performed in conditions previously found to give high degrees of Mg insertion (110°C in 0.5 Mg(TFSI) 2 in PY 14 TFSI ionic liquid electrolyte). 23,24 For the first discharge/charge cycle of the V 2 O 5 sample, the behavior resembled that observed in bulk α-V 2 O 5 previously by Yoo et al, 23 i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 This observation suggests that the V 2 O 5 -TiO 2 composite not only possessed smaller crystallite sizes than the V 2 O 5 sample, but a greater degree of crystalline disorder. 28 Electrochemical analysis of the two materials under study was performed in conditions previously found to give high degrees of Mg insertion (110°C in 0.5 Mg(TFSI) 2 in PY 14 TFSI ionic liquid electrolyte). 23,24 For the first discharge/charge cycle of the V 2 O 5 sample, the behavior resembled that observed in bulk α-V 2 O 5 previously by Yoo et al, 23 i.e.…”
Section: Resultsmentioning
confidence: 99%
“…11,23 However, we note that other spinel compounds (AM 2 O 4 , where A = Mg or Zn, M = Cr, Co, Fe, Mn, V) have also consistently demonstrated Mg removal on charge (∼200 mA h g −1 ). 14,[26][27][28][29][30][31] Comparing between these materials, the report of α-V 2 O 5 is arguably the most striking with a high capacity of 300 mA h g −1 at 110°C, where this degree of Mg intercalation was confirmed and quantified by a combination of EDS, FTIR, XRD and XAS analysis. 23 The voltage hysteresis of the first cycle (1.35 V) was significantly higher than latter cycles (0.73 V), and inspection of the α-V 2 O 5 particles revealed significant delamination of the α-V 2 O 5 layers following the first discharge: it can therefore be hypothesized that the delamination of α-V 2 O 5 reduced the observed voltage hysteresis.…”
Section: Introductionmentioning
confidence: 98%
“…This study revealed that diffusive processes impose a limit on the degree and reversibility of the observed Mg electrochemistry in ζ-V 2 O 5 , and that nanosizing can significantly improve electrode kinetics, revealing a key contribution to the voltage hysteresis that is pervasive to oxides used as Mg intercalation electrodes. 14,19,42,43 However, questions remain regarding the uniformity of magnesiation of cathode particles throughout the electrode. Therefore, it is suggested that future efforts should not only target ultrafine particles of candidate oxide electrode materials, but also probe their activity as a function of electrode depth, to elucidate kinetic limitations imposed by electrolyte permeation in the electrode and bulk electrode resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In contrast, oxide materials can offer much higher potentials vs. Mg/Mg 2+ , e.g. 2.5 V for V 2 O 5 , 14,15 2.9 V for MgMn 2 O 4 , 16 and 3.5 V for MgCr 2 O 4 , 14,15,[17][18][19] although these materials typically exhibit Mg insertion and removal kinetics that are moderateto-poor (e.g. overpotentials of >0.7 V for V 2 O 5 , corresponding to ∼70% energy efficiency).…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and experimental studies have revealed that transition-metal oxide spinels constitute a class of materials that provide possible host structures for favorable multivalent ion intercalation due to their three-dimensional pathways of migration, offering a diversity of favorable intercalation sites [3]. Initial studies have demonstrated low levels of Mg (de)intercalation into the spinel cathodes [4]. It was suggested that the sluggish intercalation chemistry during electrochemical cycling is due to structural changes and phase transitions hindering the Mg mobility and reversibility [5].…”
mentioning
confidence: 99%